Determination of the prevalence of African trypanosome species in indigenous dogs of Mambwe district, eastern Zambia, by loop-mediated isothermal amplification - Malimba Lisulo; Chihiro Sugimoto; Kiichi Kajino; Kyouko Hayashida; Macarthy Mudenda; Ladslav Moonga; Joseph Ndebe; Selestine Nzala; Boniface Namangala (Parasites & Vectors, 2014)
Abstract Background Dogs have been implicated to serve as links for parasite exchange between livestock and humans and remain an important source of emerging and re-emerging diseases including trypanosome infections. Yet, canine African trypanosomosis (CAT), particularly in indigenous dogs (mongrel breed) remains under- reported in literature. This study evaluated the performance of loop-mediated isothermal amplification (LAMP) in detecting trypanosomes in blood from indigenous dogs of tsetse-infested Mambwe district in eastern Zambia. Methods A cross sectional survey of CAT was conducted within 5 chiefdoms (Msoro, Kakumbi, Munkanya, Nsefu, Malama) of Mambwe district, eastern Zambia, during October 2012. Blood samples from 237 indigenous hunting dogs were collected and screened by microscopy and LAMP. Results Of the 237 dogs screened for CAT, 14 tested positive by microscopy (5.9%; 95% CI: 2.9 – 8.9%), all of which also tested positive by LAMP. In addition, LAMP detected 6 additional CAT cases, bringing the total cases detected by LAMP to 20 (8.4%; 95% CI: 4.9 – 12.0%). Irrespective of the detection method used, CAT was only recorded from 3 chiefdoms (Munkanya, Nsefu, Malama) out of the 5. According to LAMP, these infections were caused by Trypanosoma congolense, Trypanosoma brucei brucei and the zoonotic Trypanosoma brucei rhodesiense. Although these CAT cases generally did not manifest clinical illness, an association was observed between infection with Trypanosoma brucei subspecies and occurrence of corneal opacity. Conclusions This communication reports for the first time the occurrence of CAT in indigenous Zambian dogs. Our study indicates that LAMP is a potential diagnostic tool for trypanosome detection in animals. LAMP was more sensitive than microscopy and was further capable of distinguishing the closely related T. b. brucei and T. b. rhodesiense. In view of the sporadic cases of re-emerging HAT being reported within the Luangwa valley, detection of the human serum resistant associated (SRA) gene in trypanosomes from mongrels is intriguing and indicative of the risk of contracting HAT by local communities and tourists in Mambwe district. Consequently, there is a need for continuous trypanosome surveillances in animals, humans and tsetse flies using sensitive and specific tests such as LAMP.